Pengaruh Rekrutmen Dan Pelatihan Terhadap Kinerja Pegawai - Sukasih, Ahmad Syarifudin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine the influence of recruitment and training on performance at PT. Telkom Access North Jakarta. This study uses a quantitative analysis approach, the quantitative approach in this study is the data that has been obtained in the form of numbers that can be calculated. The data collection came from questionnaires as well as the collection of several documents related to the research. The results of the study show that recruitment partially has a significant effect on employee performance at PT. Telkom Access North Jakarta. This is evidenced by a partial hypothesis test (t-test) obtained a t-table value of > (10.349 > 1.980) and a significance value of < 0.05 (0.00 < 0.05). Training partially has a significant effect on employee performance at PT. Telkom Access North Jakarta. This is evidenced by a partial hypothesis test (t-test) obtained by a t-table >(8.177 > 1.980) and a significance value of < 0.05). Simultaneous recruitment and job training have a significant effect on employee performance at PT. Telkom Access North Jakarta. This is evidenced by a simultaneous hypothesis test (F test) obtained Fcal > Ftabel (53.813 > 3.070) and a significant value of < 0.05 (0.00 < 0.05).